Evolution of Barrier Membranes in Periodontal Regeneration-“Are the third Generation Membranes really here?" - George Sam; Baiju Radhamoni Madhavan Pillai (Journal of Clinical and Diagnostic Research, 2014)
In the last decades, Guide Tissue Regeneration (GTR) technique has been applied for the treatment of various periodontal defects such as intrabony defects, furcation involvements and localized gingival recession defects. From early days of using membranes with the simple aim of minimizing toxic response in the host, membranes have come a long way. Third generation membranes not only act as barriers but also as delivery devices to release specific agents. Many clinical trials have focused on using membranes as delivery devices for antibiotics and growth factors. In this article we take a brief look at the evolution of barrier membranes and future avenues with regard to third generation membranes.